Composite wiping material as well as preparation method and application thereof
By combining the meltblown fiber mesh with two polypropylene resins as substrates with nonwoven materials, the skin irritation, water pollution and object damage problems in the improvement of decontamination capacity of existing wipe materials is solved, and efficient and safe Wiping effect, suitable for use in various scenarios.
Patent Information
- Application Number
- CN202411486102.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
AI Technical Summary
In the process of improving the decontamination ability, existing wipe materials are prone to skin irritation, water pollution and damage to the surface of the wiped object, and it is difficult to meet the needs of various scenarios.
The composite wipe material is used to combine meltblown fiber webs with two polypropylene as the matrix and nonwoven materials. By improving the composition and production process of the meltblown fiber webs, the surface friction and mechanical strength of the material are enhanced.
It achieves a wiping effect without hair loss and excellent mechanical strength, and does not damage the surface of the wiped object. It can save the use of surfactant and is suitable for cleaning needs in various scenarios.
Smart Images

Figure CN119388848A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a composite wiping material and a preparation method and application thereof, belonging to the technical field of wiping materials. Background Art
[0002] At present, wiping materials are widely used in life, industry and other fields, such as kitchen wipes, lazy rags, shoe wipes, machine repair wipes, etc. In order to achieve higher decontamination ability, traditional wiping materials, on the one hand, add more surfactants such as detergents and bleaches, but adding too much surfactant will cause skin irritation and water pollution. On the other hand, materials similar to steel wool are used to enhance friction, but it is easy to damage the surface of the object being wiped. Therefore, all the above methods have their disadvantages.
[0003] In daily life, spunlace nonwoven materials are widely used in wipes. By adding surface patterns of spunlace nonwoven materials, such as pearl patterns, the surface friction of wipes is enhanced, but the effectiveness of this method is limited. In industrial scenarios, polypropylene meltblown fiber materials are widely used because polypropylene materials have natural oleophilic and hydrophobic properties. However, polypropylene meltblown fibers are prone to hair loss and have low mechanical strength. Currently, Li Shihuang and others have proposed adding a spunbond long fiber web between the meltblown fiber web and the wood pulp fiber web. On the one hand, it can prevent the "hair loss" phenomenon, and on the other hand, it can enhance the mechanical strength of the material. The products made by this method are softer and are mainly used for infant care. They cannot be used in wiping scenarios that require moderate friction.
[0004] Therefore, there is currently a lack of a wiping material that can be used in more scenarios, has a good wiping effect, does not shed hair, and has excellent mechanical strength. Summary of the invention
[0005] In order to solve the above problems, a composite wiping material is provided, which is composed of a meltblown fiber web with two polypropylene bases and a non-woven material. The composite wiping material can meet the needs of complex scenarios, does not shed and has excellent mechanical strength. The surface friction of the material is enhanced by improving the composition and production process of the meltblown fiber web. Not only does it not damage the surface of the wiped object during wiping, but it also saves the use of surfactants.
[0006] According to one aspect of the present application, a method for preparing a composite wiping material is provided, comprising the following steps:
[0007] (1) Refining, slicing and drying 10-40 parts of a first polypropylene resin, 50-80 parts of a second polypropylene resin, 5-10 parts of a polyurethane resin and 1-3 parts of a polyethylene wax by weight to obtain a microphase separation blended melt-blown special material, wherein the melt mass flow rate of the first polypropylene resin is 10-500 g / 10 min, and the melt mass flow rate of the second polypropylene resin is 1000-3000 g / 10 min;
[0008] (2) the microphase separation blended melt-blown special material is fed into an extruder for melting and extrusion to obtain a melt, filtered, metered and transported to a melt-blown die head for extrusion to obtain fibers, and the fibers are initially cooled to form fiber bundles distributed on a mesh belt receiver, wherein the mesh belt has a porosity of not less than 27%, to form a melt-blown fiber web;
[0009] (3) Compounding a nonwoven material onto the meltblown fiber web to form a composite wiping material.
[0010] Spinning the above two polypropylene resins with large fluidity differences will produce a granular feel and enhance the wiping force of the composite wiping material. The added polyurethane can increase the toughness of the meltblown fiber web and the bonding points between the fibers. If the amount of polyurethane added is too little, the toughness of the composite wiping material will be insufficient, making it easy to break during the wiping process, and it will also lead to insufficient oil and water absorption. Polyethylene wax can lubricate the two polypropylene resins, solve the technical problem of poor compatibility of the two polypropylene resins with large fluidity differences, improve the smoothness of spinning, and within the above range, it will also improve the uniformity of the granular feel formed by the meltblown fiber web. However, if too much is added, the granular feel of the meltblown fiber web will be reduced, thereby reducing the wiping performance of the composite wiping material, and it will also reduce the mechanical properties of the composite wiping material.
[0011] Under the above ingredients, the spun fiber filaments are evenly stacked on the mesh belt with a porosity ≥ 27%. Since the fiber layer has not been completely solidified, it is tightly attached to the mesh belt under the action of upper hot air and lower suction air. The larger pores can increase the three-dimensional structure of the meltblown fiber web, increase the thickness of the meltblown fiber web, and increase the surface roughness of the meltblown fiber web.
[0012] Preferably, the first polypropylene resin is 15 parts and the second polypropylene resin is 79 parts.
[0013] Optionally, in step (1), a twin-screw extruder is used for refining, and the temperature of each zone of the barrel is set as follows: 180-200°C in zone 1, 200-210°C in zone 2, 220-260°C in zone 3, 220-260°C in zone 4, 220-260°C in zone 5, and 220-260°C in zone 6.
[0014] Optionally, the meltblown fiber web has a gram weight of 15-150 g / m 2, thickness is 0.5-1.7mm;
[0015] The diameter of the fibers in the meltblown fiber web is 3 μm-60 μm.
[0016] Optionally, the nonwoven material has a thickness of 0.1-1.0 mm and a gram weight of 10-80 g / m 2 , transverse / longitudinal breaking strength>3N, transverse / longitudinal breaking elongation<110%, longitudinal / transverse strength ratio<3, transverse / longitudinal strength ratio<3.
[0017] Optionally, the nonwoven material is selected from at least one of 100% polyester spunlace nonwoven material, polyester / viscose fiber spunlace nonwoven material, 100% viscose spunlace nonwoven material, wood pulp / PP spunlace nonwoven material, wood pulp / PET spunlace nonwoven material, polypropylene spunbond nonwoven material, polyester spunbond nonwoven material and polyethylene spunbond nonwoven material.
[0018] Optionally, the temperature of each zone of the extruder barrel in step (2) is set as: 180-200°C in zone 1, 200-210°C in zone 2, 220-260°C in zone 3, 220-260°C in zone 4, 220-260°C in zone 5, and 220-260°C in zone 6.
[0019] Optionally, the temperature of the meltblowing die head is 210-270°C, the process hot air temperature is 230-280°C, the screw fan frequency is 90-135Hz, and the DCD is 100-210mm.
[0020] Optionally, the combination of the composite nonwoven material on the meltblown fiber web in step (3) is selected from any one of the following:
[0021] i) a combination of a layer of meltblown fiber web and a layer of nonwoven material;
[0022] ii) a combination of two layers of meltblown fiber web with a layer of nonwoven material sandwiched between them;
[0023] iii) a combination of two layers of meltblown fiber webs with two layers of nonwoven material sandwiched between them;
[0024] iiii) a combination of two layers of nonwoven material with a layer of meltblown fiber web sandwiched between the outer sides;
[0025] iiiii) A combination of two layers of nonwoven material with a layer of meltblown fiber web sandwiched between them.
[0026] Optionally, the moisture content of the micro-phase separation blended melt-blown special material is 0.1-0.5%.
[0027] Optionally, the composite nonwoven material on the meltblown fiber web in step (3) is formed by hot rolling bonding and / or ultrasonic bonding and / or adhesive bonding in the presence of an adhesive.
[0028] Preferably, the temperature of the hot rolling bonding is 50-200°C, the pressure is 0.01MPa-5MPa, and the line speed is 1-80m / min;
[0029] The frequency of the ultrasonic bonding is 13KHz-15KHz, the pressure is 0.05MPa-0.3MPa, and the line speed is 5-30m / min.
[0030] The adhesive bonding is a thermoplastic adhesive or a thermosetting adhesive;
[0031] Preferably, when a thermoplastic adhesive is used, the amount of adhesive applied is 1.0-15 g / m 2 , the glue barrel temperature is 110-200℃, the throat temperature is 130-210℃, the glue gun temperature is 130-210℃, the composite extrusion pressure is 0.05MPa-0.8MPa, and the line speed is 5-200m / min;
[0032] When using thermosetting adhesive, the amount of adhesive applied is 3-15g / m 2 , the glue barrel temperature is 80-200℃, the throat temperature is 90-210℃, the glue gun temperature is 90-210℃, the composite extrusion pressure is 0.05MPa-0.8MPa, the pressure roller temperature is 110-180℃, the line speed is 5-300m / min, and the curing time is 2-24h.
[0033] Optionally, the thermoplastic adhesive is selected from at least one of polyurethane, polyvinyl acetate, polyacrylate, polyvinyl chloride-vinyl acetate, polystyrene, polyamide, polyethylene, and polyvinyl chloride, and the thermosetting adhesive is selected from at least one of silicone, polyisocyanate, reactive polyurethane, phenolic resin, acrylic diester, unsaturated polyester, and urea-formaldehyde resin.
[0034] The three methods of hot rolling bonding, ultrasonic bonding, and adhesive bonding will firmly combine the meltblown fiber web and nonwoven materials together, and will not easily delaminate. Hot rolling bonding and ultrasonic bonding are to locally melt the meltblown fiber web and the nonwoven material itself, and then cool them together. Rollers and flower rollers with different patterns can be selected. Adding graphics to the surface of the composite wiping material, and the "concave" points / lines formed after bonding can also enhance the roughness of the composite material surface and increase the wiping effect of the composite wiping material. Adhesive bonding can also firmly combine the meltblown fiber web and the nonwoven material, and there are more bonding points between the materials, and the bonding is stronger. On the other hand, the use of adhesive bonding can fully retain the fabric texture of the meltblown fiber web and the nonwoven material, and play their respective roles in the use scenario of the composite wiping material.
[0035] According to another aspect of the present application, a composite wiping material prepared by the method for preparing the composite wiping material described in any one of the above is provided.
[0036] According to another aspect of the present application, an application of the composite wiping material described above is provided.
[0037] The composite wiping material can be directly used for wiping without a cleaning agent, for example, for cleaning stoves, tableware, pots, wiping greasy hands, cleaning tea tables and tea sets, cleaning tiles and bathrooms, cleaning stubborn stains on car surfaces, cleaning shoe uppers, etc.
[0038] The beneficial effects of this application include but are not limited to:
[0039] 1. The preparation method of the composite wiping material of the present application is simple, and a melt-blown fiber web having a "granular" frosted effect on the surface can be obtained through a melt-blowing process. Therefore, the wiping effect of the composite wiping material can be enhanced, and effective cleaning can be achieved without the presence of a detergent, and oil stains can be effectively absorbed, and it is more suitable for removing sticky or stubborn oil stains.
[0040] 2. The composite wiping material prepared in the present application combines a meltblown fiber web with a nonwoven material, which can not only make up for the shortcomings of insufficient strength of the meltblown fiber web and insufficient wiping power of the nonwoven material, but also can meet the use in more scenarios, ensure the wiping effect while avoiding damage to the surface of the wiped object, and is suitable for large-scale promotion and use.
[0041] 3. The composite wiping material prepared in the present application has the advantages of simple and easy-to-obtain raw materials, low production cost, high mechanical strength, no hair shedding, and dirt can be removed by easy wiping.
[0042] 4. The composite wiping material prepared in the present application can be used for wiping directly without adding a detergent, or it can be used for wiping after absorbing a detergent, so as to meet more usage requirements; when absorbing the detergent, it can increase the adsorption capacity of the detergent to ensure that the detergent exerts a better effect, and can improve the adsorption capacity of oil stains and stains during the wiping process.
[0043] 5. The composite wiping material prepared in the present application can be reused multiple times after being cleaned with clean water after absorbing oil stains, thereby improving the utilization rate of the composite wiping material and reducing the wiping cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0045] Figure 1This is a schematic diagram of the meltblown fiber web involved in Example 1 of the present application.
[0046] Figure 2 This is a schematic diagram of the scanning electron microscope involved in Example 4 of the present application.
[0047] Figure 3 This is a cross-sectional view of the composite wiping material involved in Example 1 of the present application. DETAILED DESCRIPTION
[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0049] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application were purchased through commercial channels.
[0050] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.
[0051] Example 1
[0052] Step 1: Preparation of microphase separation blending melt-blown special materials:
[0053] 15 parts of the first polypropylene resin, 79 parts of the second polypropylene resin, 5 parts of polyurethane resin, and 1 part of polyethylene wax were placed in a twin-screw extruder, and the barrel temperature was set as follows: 190°C in barrel zone 1, 210°C in barrel zone 2, 230°C in barrel zone 3, 230°C in barrel zone 4, 230°C in barrel zone 5, and 230°C in barrel zone 6, and the die temperature was set at 220°C. The strips were sliced after water cooling and natural cooling, and then entered the drying bin, the drying bin temperature was set at 95°C, and the drying time was 4 hours, to obtain a micro-phase separation blended melt-blown special material with a moisture content of 0.1-0.5%.
[0054] Step 2: Preparation of meltblown fiber web:
[0055] The microphase separation blended melt-blown special material obtained in step one is passed through a melt-blown feeding system and enters an extruder for melt extrusion. The temperature of each zone of the extruder barrel is set as follows: 180°C for zone one, 210°C for zone two, 220°C for zone three, 230°C for zone four, 230°C for zone five, and 230°C for zone six; the melt is then transported to a melt filter for filtration, and then enters a metering pump; under the action of the metering pump, the melt is quantitatively output and enters a melt-blown die head, and the temperature of the melt-blown die head is set as follows: 270°C for zone one, 270°C for zone two, 260°C for zone three, 255°C for zone four, 245°C for zone five, 240°C for zone six, 245°C for zone seven, 255°C for zone eight, 260°C for zone nine, 270°C for zone ten, and 270°C for zone eleven.
[0056] Finally, after the melt flow is extruded from the meltblown die head, it is stretched and shaped by the hot air of the drafting air duct to form fibers. After the fibers are initially cooled by the side-blown cold air, the formed fiber bundles are distributed on the mesh belt with a porosity of more than 35%. The process hot air temperature is 250°C, the screw fan frequency is 127Hz, and the DCD is 210mm. Finally, a meltblown fiber web with a gram weight of 27g / ㎡ and a "granular" frosted effect is produced.
[0057] Step 3: Production of composite wiping materials:
[0058] A layer of meltblown fiber web prepared in step 2 is combined with a layer of polyester spunlace nonwoven material to form a composite wiping material by bonding with an adhesive. The glue gun temperature is 145° C., the pressure is set to 0.3 MPa, and the line speed is 15 m / min.
[0059] Examples 2-8 and Comparative Examples 1-5 prepare different composite wiping materials according to the same process as Example 1. The specific process differences are shown in Tables 1 and 2 below. Comparative Example 5 refers to the preparation of the composite wiping materials by using only two layers of all-polyester spunlace nonwoven materials instead of preparing the meltblown fiber web. In Tables 1 and 2, the first polypropylene resin MFR refers to the melt mass flow rate of the first polypropylene resin, the test conditions are 230°C and 2.16kg pressure, and the unit is g / 10min; the second polypropylene resin MFR refers to the melt mass flow rate of the second polypropylene resin, the test conditions are 230°C and 2.16kg pressure, and the unit is g / 10min; the transverse / longitudinal breaking strength of the nonwoven material is greater than 3N, the transverse / longitudinal breaking elongation is less than 110%, the longitudinal / transverse strength ratio is less than 3, and the transverse / longitudinal strength ratio is less than 3.
[0060] Table 1
[0061]
[0062]
[0063] Table 2
[0064]
[0065]
[0066] Note: The examples and comparative examples directly give the gram weight data of the meltblown fiber web, and do not directly list the set process parameters of the device / equipment / production line. This is because the gram weight of the meltblown product is determined by the extrusion volume of the production equipment and the linear speed of the mesh belt. Therefore, the gram weight in Table 1 and Table 2 can be adjusted as needed, which is common knowledge in the industry.
[0067] Example 9
[0068] The difference between this embodiment and embodiment 1 is that the weight of the meltblown fiber web is 180 g / m 2 , the rest is the same as Example 1.
[0069] Example 10
[0070] The difference between this embodiment and embodiment 1 is that the weight of the meltblown fiber web is 10 g / m 2 , the rest is the same as Example 1.
[0071] Embodiment 11
[0072] The difference between this embodiment and embodiment 1 is that the thickness of the meltblown fiber web is 0.3 mm, and the rest is the same as embodiment 1.
[0073] Example 12
[0074] The difference between this embodiment and embodiment 1 is that the thickness of the meltblown fiber web is 2.0 mm, and the rest is the same as embodiment 1.
[0075] Test Example 1
[0076] The schematic diagram of the meltblown fiber web of Example 1 is shown in Figure 1 It can be seen that the meltblown fiber web is distributed very densely and evenly, and has a granular shape. The cross-sectional view of the composite wiping material prepared in Example 1 is shown in Figure 3 It can be seen that the meltblown fiber web and the nonwoven material are well composited. The composite material of Example 4 was analyzed by scanning electron microscope, and the test picture is shown in Figure 2 It can be seen that the diameter of the fibers in the meltblown fiber web is in the range of 3μm-60μm, and the distribution of the overall meltblown fiber web is relatively uniform.
[0077] The following tests were performed on the composite wiping materials prepared in the above embodiments and comparative examples. The test results are shown in Table 3.
[0078] 1. Test the oil absorption multiple of the composite wiping material according to FZT01130-2016: the oil used is engine oil, record the weight W0 of the composite wiping material before oil absorption, and the weight W1 after oil absorption, and the oil absorption multiple = (W1-W0) / W0×100.
[0079] 2. Water absorption rate: Test the composite wiping material according to the test method in GB / T 21655.1-2023, and record the ratio of the water absorption weight to the weight of the composite wiping material.
[0080] 3. Surface roughness: The composite wiping material was tested according to the test method in GB / T 3505-2000. The instrument used was a stylus profilometer. Ra and Rz data were recorded, where Ra represents the arithmetic mean deviation of the profile and Rz represents the maximum height of the profile.
[0081] 4. Breaking strength and elongation at break: Test the dry composite wiping material according to the method in GB / T24218.3-2010, and record the breaking strength and elongation at break.
[0082] Table 3
[0083]
[0084]
[0085] According to the data in the above table, it can be seen from the comparison of the test data of Comparative Example 1 with the test data of Example 1 that the roughness of the material without adding the first polypropylene meltblown fiber web is greatly reduced, and a good wiping effect cannot be achieved; at the same time, by comparing the data of Example 7, it can be seen that when a lower meltblown fiber web weight is used, the roughness of the composite wiping material is between Example 1 and Comparative Example 1, and the sample has a weaker "granular feel" and can be used for pet bath towels.
[0086] According to the comparison between Example 9, Example 10 and Example 1, it can be known that the gram weight of the meltblown fiber web is related to the oil absorption performance and surface roughness of the wiping material. If the gram weight is too low, the oil absorption of the wiping material is poor, and the surface roughness is low, and the matte feeling is not good. If the gram weight is too high, the water absorption performance of the wiping material becomes poor. Although the surface roughness is large, it is also easy to reduce the user experience. Therefore, it is necessary to maintain a moderate surface roughness.
[0087] According to the comparison between Example 11, Example 12 and Example 1, under the same conditions, the thickness of the meltblown fiber web will affect various performances of the composite wiping material. If the thickness is too thick, the surface roughness of the wiping material will increase, but too high a roughness will reduce the user experience and scratch the skin. If the thickness is too thin, the surface roughness of the wiping material will be too low and cannot achieve a good wiping effect.
[0088] According to the comparison between Comparative Example 2 and Example 1, due to the lack of polyurethane resin in the raw materials, the elongation at break of the meltblown fiber web drops sharply, the sample lacks "toughness", and the wiping effect also decreases.
[0089] According to the comparison between Comparative Example 3 and Example 1, it can be seen that since no polyethylene wax is added to the raw materials, it is difficult to balance the two polypropylenes with a large difference in melt mass flow rate (viscosity), resulting in spinning difficulties. The surface roughness of the composite wiping material is high, but the uniformity of the granularity is poor, so the mechanical strength and wiping strength will also decrease.
[0090] According to the comparison between Comparative Example 4 and Example 1, it can be seen that the use of a low-porosity mesh belt results in a low thickness of the meltblown fiber web, a low surface roughness of the composite wiping material, and a poor wiping effect.
[0091] Comparative Example 5 is a blank control test. The oil absorption multiple and surface roughness of the composite wiping material prepared without using the meltblown fiber web of the present application are smaller than those of other embodiments and comparative examples.
[0092] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a composite wiping material, characterized in that: The steps include: (1) Refining, slicing and drying 10-40 parts of a first polypropylene resin, 50-80 parts of a second polypropylene resin, 5-10 parts of a polyurethane resin and 1-3 parts of a polyethylene wax by weight to obtain a microphase separation blended melt-blown special material, wherein the melt mass flow rate of the first polypropylene resin is 10-500 g / 10 min, and the melt mass flow rate of the second polypropylene resin is 1000-3000 g / 10 min; (2) the microphase separation blended melt-blown special material is fed into an extruder for melting and extrusion to obtain a melt, filtered, metered and transported to a melt-blown die head for extrusion to obtain fibers, and the fibers are initially cooled to form fiber bundles distributed on a receiver mesh belt, wherein the mesh belt has a porosity of not less than 27%, to obtain a melt-blown fiber web; (3) Compounding a nonwoven material onto the meltblown fiber web to form a composite wiping material.
2. The preparation method according to claim 1, characterized in that: The meltblown fiber web has a grammage of 15-150 g / m 2 , thickness is 0.5-1.7mm.
3. The preparation method according to claim 1, characterized in that: The diameter of the fibers in the meltblown fiber web is 3 μm-60 μm.
4. The preparation method according to claim 1, characterized in that: The nonwoven material has a thickness of 0.1-1.0 mm and a gram weight of 10-80 g / m 2 , transverse / longitudinal breaking strength>3N, transverse / longitudinal breaking elongation<110%, longitudinal / transverse strength ratio<3, transverse / longitudinal strength ratio<3.
5. The preparation method according to claim 1, characterized in that: The nonwoven material is selected from at least one of 100% polyester spunlace nonwoven material, polyester / viscose fiber spunlace nonwoven material, wood pulp / PP spunlace nonwoven material, wood pulp / PET spunlace nonwoven material, polypropylene spunbond nonwoven material, polyester spunbond nonwoven material and polyethylene spunbond nonwoven material.
6. The preparation method according to claim 1, characterized in that: The combination of the composite nonwoven material on the meltblown fiber web in step (3) is selected from any one of the following: i) a combination of a layer of meltblown fiber web and a layer of nonwoven material; ii) a combination of two layers of meltblown fiber web with a layer of nonwoven material sandwiched between them; iii) a combination of two layers of meltblown fiber webs with two layers of nonwoven material sandwiched between them; iiii) a combination of two layers of nonwoven material with a layer of meltblown fiber web sandwiched between the outer sides; iiiii) A combination of two layers of nonwoven material with a layer of meltblown fiber web sandwiched between them.
7. The preparation method according to claim 1, characterized in that: The moisture content of the micro-phase separation blended melt-blown special material is 0.1-0.5%.
8. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the meltblowing die head is 210-270° C., the process hot air temperature is 230-280° C., the screw fan frequency is 90-135 Hz, and the DCD is 100-210 mm; The method of bonding the meltblown fiber web with the composite nonwoven material in step (3) is thermal calendering bonding and / or ultrasonic bonding and / or adhesive bonding.
9. The composite wiping material prepared by the method for preparing the composite wiping material according to any one of claims 1 to 8.
10. Use of the composite wiping material according to claim 9.
Citation Information
Patent Citations
Production and producer for functional modified microgranular melt-jetting non-woven cloth
CN101029433A
High-permeability and high-elongation non-woven fabric composite material and preparation method thereof
CN106835506A
Wear-resisting wiping towel and manufacturing method thereof
CN109554824A
Wiping towel and manufacturing method thereof
CN109667063A
Composite Wipes and Fabrication Method Therefor
US20240052538A1
Cited By
Composite wiping material and preparation method thereof
CN122353999A